Manajemen Pembelajaran Tema Wedding Organizer Menggunakan Metode PJBL - Risna Rahmawati; Badrudin Badrudin (AFKARINA: Jurnal Pendidikan Agama Islam, 2022)
This study aims to describe the wedding organizer theme learning management using the PJBL method at SMKN 15 Bandung. More specifically, this study aims to: (1) describe the preparation of wedding organizer theme lesson plans using the PJBL method at SMKN 15 Bandung; (2) describe the implementation of the Wedding Organizer theme learning using the PJBL method at SMKN 15 Bandung; 3) describe the results of the Wedding Organizer theme learning assessment using the PJBL method at SMKN 15 Bandung. This research uses a qualitative approach with descriptive methods. Researchers become key instruments in research. Collecting data using observation techniques, interviews, documentation and triangulation. Based on the results of the research, it was found that in terms of planning the theme of Wedding Organizer using the PJBL method at SMKN 15 Bandung in general it had been implemented well. Related to the implementation phase is in accordance with the planning. Finally, the results processing stage was carried out well by converting scores into scores which were carried out directly by the assessment team, while follow-up in the form of remedial and enrichment was not carried out.